Household Consumers Perception towards Frozen Beef - Astari Apriantini; Irma Isnafia Arief; Lucia cyrilla ENSD (Jurnal Ilmu Ternak dan Veteriner, 2022)
Demand of beef in Indonesia is higher compared to the domestic beef supply, hence the Indonesian government has established policy to import frozen beef from other countries in order to support the high demand of Indonesia people. However, mosf of Indonesian people prefer to purchase fresh meat (freshly slaughtered beef) rather than frozen beef. The aims of this study were to identify the characteristics of household consumers who bought beef meat and their perceptions towards frozen beef; including to analyze the relationship between perceptions and consumer characteristics of frozen beef, and to analyze the consumer behavior in making decision to buy frozen beef in Bogor area and DKI Jakarta. Total about 200 households were directly interviewed using structured questionnaire. The questionnaires includes general characteristics of respondents (age, education level, occupation, income, number of family member), purchasing behavior which was analyzed descriptively, and respondents perceptions toward frozen beef which was analyzed by calculating the average value of perception and then categorized based on the level of perception category. Results showed that consumer’s perceptions toward frozen beef according to several aspects had a low score (average final score 2.37), indicated that consumers had a poor perceptions towards frozen beef. Furthermore, most of the respondents who buy beef were housewives who buy meat in traditional markets which only provide fresh meat, they assumed that fresh meat had very good quality because the meat came from slaughtered beef.  Those respondents think that freezing causes negative effects on beef, freezing treatment reduce the quality such as changes of meat color and flavour; and reduce nutritional content of beef.  It was discovered that socialization about frozen beef and the process of handling frozen meat is required for household consumers to control the quality of beef as well as to increase the consumer’s trusts in purchasing frozen beef.